2011
DOI: 10.1002/cphc.201100055
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Assisted Covalent Binding of Graphene to an Amorphous Silica Surface: A Theoretical Prediction

Abstract: We propose a mechanism for defect-assisted covalent binding of graphene to the surface of amorphous silica (a-SiO(2)) based on first-principles density functional calculations. Our calculations show that a dioxasilirane group (DOSG) on a-SiO(2) may react with graphene to form two Si-O-C linkages with a moderate activation barrier (≈0.3 eV) and considerable exothermicity (≈1.0 eV). We also examine DOSG formation via the adduction of molecular O(2) to a silylene center, which is an important surface defect in a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Using this approach, sufficient densities of various defect sites could be prepared on high surface area silica to enable characterization of these sites using IR and photoluminescence (PL) spectroscopies. However, intrinsic defect sites are much more difficult to detect. Because of the challenge of experimentally detecting low-density intrinsic defect sites on the silica surface, computational studies of such sites have been performed. Kuo and Hwang found that a surface OVD is capable of transforming from a Si–Si dimer to other reactive structures, including silylene and silanone sites …”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, sufficient densities of various defect sites could be prepared on high surface area silica to enable characterization of these sites using IR and photoluminescence (PL) spectroscopies. However, intrinsic defect sites are much more difficult to detect. Because of the challenge of experimentally detecting low-density intrinsic defect sites on the silica surface, computational studies of such sites have been performed. Kuo and Hwang found that a surface OVD is capable of transforming from a Si–Si dimer to other reactive structures, including silylene and silanone sites …”
Section: Introductionmentioning
confidence: 99%